Application of vertical seismic profiling for the characterisation of hard rock - Greenwood, Andrew John (Curtin University, 2013)
Seismic imaging in hard rock environments is gaining wider acceptance as a mineral exploration technique and as a mine-planning tool. However, the seismic images generated from hard rock targets are complex due to high rock velocities, low contrasts in elastic rock properties, fractionated geology, complicated steep dipping structures and mineralogical alterations. In order to comprehend the complexity and utilise seismic images for structural mapping and rock characterisation, it is essential to correlate these images to known geology. An ideal tool for this purpose is Vertical Seismic Profiling or VSP. The VSP method can provide not only a means to correlate seismic images to geology but also to study the properties of the transmitted seismic field as it is modified by different rock formations, the origin of the reflected events and the corresponding reflector geometry. However, the VSP technique is rarely used in hard rock environments because of the cost and operational issues related to using clamping geophones in exploration boreholes, which are 96 mm or less in diameter. Consequently the main objective of this research is to produce an efficient VSP methodology that can be readily deployed for mineral exploration.An alternative to the clamping geophone is the hydrophone. Hydrophones are suspended in, and acoustically coupled to the borehole wall through, the borehole fluid. Borehole acoustic modes known as "tube-waves" are generated by seismic body waves passing the water column and are guided in the borehole due to the high acoustic impedance contrast between the rock and fluid. Tube-waves are 1-2 orders in magnitude higher in amplitude than seismic signal and mask reflected energy in hydrophone VSP profiles. As such the use of borehole hydrophone arrays to date has been restricted to direct body wave measurements only. I have effectively mitigated tube-waves in hydrophone VSP surveys with specific acquisition methodologies and refined signal processing techniques. The success of wavefield separation of tubewaves from hydrophone data depends critically upon; having high signal to noise ratio, well sampled data, pre-conditioning of the field data and processing in the field record (FFID) domain. Improvements in data quality through the use of high viscosity drilling fluids and baffle systems have been tested and developed. The increased signal to noise ratio and suppression of tube-wave energy through these technologies greatly enhances the performance of hydrophone VSP imaging.Non-standard wavefield separation techniques successfully removed strong coherent tube-wave noise. The additional wavefield separation steps required to remove high amplitude tube-waves does degrade the overall result with some fidelity and coherency being lost. However, a direct comparison of hydrophone and borehole clamping geophone VSP surveys has been conducted in the Kambalda nickel district and the two methodologies produced comparable results. The difference was that the hydrophone data were collected in a fraction of the time compared to clamping geophone equipment with significantly less risk of equipment loss and with reduced cost.The results of these field experiments and the data processing methodology used, demonstrate the potential of hydrophone VSP surveys in the small diameter boreholes typical of hard rock exploration. Thus, these results show that hydrophone VSP is a viable, cost effective and efficient solution that should be employed more routinely in hard rock environments in order to enhance the value of the surface seismic datasets being acquired.